2005
DOI: 10.1592/phco.2005.25.7.924
|View full text |Cite
|
Sign up to set email alerts
|

Medical and Pharmacy Expenditures After Implementation of a Cyclooxygenase-2 Inhibitor Prior Authorization Program

Abstract: Among members denied coverage for a COX-2 inhibitor after implementation of a PA program, pharmacy costs declined without a medical cost increase associated with gastrointestinal diagnoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…A comparison group was identified from a different commercially insured BCBS population in the central United States reduced nonpreferred agent utilization and expenditures; however, it was unclear in these studies whether patients were impacted positively or negatively. 4 The PA policies evaluated in the systematic review, [5][6][7][8][9][10][11][12][13] and the studies of PA policies published after the review, consistently focus on the populations with high pharmacy spending. [14][15][16][17][18] For example, Zhang et al reported in 2009 the results of a PA policy among Medicaid and Medicare enrollees affecting second-generation antipsychotics and anticonvulsant medication.…”
Section: ■■ Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparison group was identified from a different commercially insured BCBS population in the central United States reduced nonpreferred agent utilization and expenditures; however, it was unclear in these studies whether patients were impacted positively or negatively. 4 The PA policies evaluated in the systematic review, [5][6][7][8][9][10][11][12][13] and the studies of PA policies published after the review, consistently focus on the populations with high pharmacy spending. [14][15][16][17][18] For example, Zhang et al reported in 2009 the results of a PA policy among Medicaid and Medicare enrollees affecting second-generation antipsychotics and anticonvulsant medication.…”
Section: ■■ Methodsmentioning
confidence: 99%
“…5,6,11,12,17,18,27 These studies have found no increase in medical utilization or costs among individuals denied drug coverage. A commonality of these studies was the nonacuity of the condition for which the medication is generally used.…”
Section: ■■ Conclusionmentioning
confidence: 98%
“…[16][17][18][19][20][21] A claims analysis reviewing step therapy for antidepressants showed that the days supplied and medication cost decreased, but overall and mental health-related inpatient and emergency room utilization and costs increased for employer plans. 16 A 1998 study found that common utilization management strategies for decreasing drug expenditures (e.g., restrictiveness of formulary) may be associated with higher severity-adjusted resource utilization for select conditions and that this pattern is more pronounced in the elderly.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…17 However, studies for COX-2 inhibitors show savings in pharmacy expenditure without increases in medical expenditure. [18][19][20][21] To our knowledge, no published studies have examined the impact of utilization management strategies on the use of chronic gout treatment or its effect on overall health care utilization and costs. This is understandable, since treatment options for chronic gout management are limited, and until the introduction of febuxostat, all medications had long been available as generics.…”
Section: ■■ Conclusionmentioning
confidence: 99%
“…With respect to the former, studies of the impact of PA and step therapy on medical and/or total cost of care (pharmacy and medical cost) have shown mixed results with respect to overall savings. [8][9][10][11][12][13][14][15][16][17] Recently, 2 Pfizer-sponsored retrospective studies examining the association of a pregabalin PA on the total cost of care in a Medicaid and a commercial population were presented to the MCO. [16][17] Because the MCO did not believe that the studied population was representative of its beneficiaries, Pfizer and impact of a PA on pregabalin, not a direct comparison of treatment effects of specific medications.…”
Section: A Case Study In Neuropathic Painmentioning
confidence: 99%